Immunity and vaccines against sexually transmitted Chlamydia trachomatis infection - Howie, Sarah E. M. (2011)
PURPOSE OF REVIEW: To review recent findings on immunity and vaccine development to Chlamydia trachomatis. RECENT FINDINGS: There is increasing knowledge on the interactions between Chlamydia trachomatis and infected host cells. During genital infection the organism avoids generating protective immunity but immune responses to a number of chlamydial proteins have been associated with reproductive tract pathology. Various vaccine and adjuvant preparations have been tried experimentally. Information generated by proteomics and complex studies of serological and T-lymphocyte immune responses points to novel vaccine candidates. SUMMARY: Chlamydia trachomatis, an obligate intracellular bacterium, is the commonest sexually transmitted infection worldwide and is associated with reproductive pathology. To develop rational vaccines it is necessary to understand the complex life-cycle of the organism, the host immune response to infection and how these relate to disease. Infection does not prevent reinfection and antibiotic treatment prevents antibody production at a population level. It remains unclear what type of immune response would be sufficient to prevent infection and/or reinfection. Although the prevalence and demographics of infection and the severity of disease associations suggest it would be desirable, there is no vaccine currently available. A number of studies have identified novel vaccine candidates.